2019
DOI: 10.3168/jds.2018-15649
|View full text |Cite
|
Sign up to set email alerts
|

Field study on bovine paratuberculosis using real-time PCR and liquid culture for testing environmental and individual fecal samples implemented in dairy cow management

Abstract: fecal samples using the liquid culture. Using fecal PCR, we revealed 43 positive samples of which 39 also tested positive in the liquid culture, revealing MAP-positive cows in all 3 herds. The fecal PCR procedure allows rapid detection of MAP-specific DNA with 74% of the sensitivity of liquid culture. For the purpose of testing with maximal sensitivity, cultivation in liquid medium is recommended. Cultivation of MAP in liquid medium M7H9C means a significant time gain in comparison to cultivation on solid medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Future experiments should also include feces collection and tests for paratuberculosis based on culture and PCR [ 30 , 31 , 32 ]. In recent field studies of dairy cows, fecal examination by real-time PCR testing of MAP-specific DNA was found to have 74% sensitivity of culture [ 33 ]. In recent studies, peptide magnetic separation PCR test (PMS-PCR) was found to obtain greater sensitivity and lower specificity than ELISA for paratuberculosis diagnosis [ 34 ], which indicates that this method has potential.…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments should also include feces collection and tests for paratuberculosis based on culture and PCR [ 30 , 31 , 32 ]. In recent field studies of dairy cows, fecal examination by real-time PCR testing of MAP-specific DNA was found to have 74% sensitivity of culture [ 33 ]. In recent studies, peptide magnetic separation PCR test (PMS-PCR) was found to obtain greater sensitivity and lower specificity than ELISA for paratuberculosis diagnosis [ 34 ], which indicates that this method has potential.…”
Section: Discussionmentioning
confidence: 99%
“…El cultivo en medio líquido a base de caldo Middlebrook 7H9 tiene mayor sensibilidad ARTÍCULOS ORIGINALES en comparación con el medio sólido, que es comúnmente utilizado. Los resultados son confiables y en la mitad del tiempo, con bajos costos, por lo que puede automatizarse en laboratorio (Schwalm et al, 2019) Por medio de la PCR se puede llegar a una especificidad alta, hasta del 60 % y una sensibilidad entre el 97 % y el 99 %. Sin embargo, su aplicabilidad es costosa y limitada.…”
Section: Métodos De Diagnósticounclassified